Ambiguity and the centipede game: Strategic uncertainty in multi-stage games - Jürgen Eichberger; Simon Grant; David Kelsey (University of Heidelberg, Department of Economics, 2017)
We propose a solution concept for a class of extensive form games with ambiguity. Specifically we consider multi-stage games. Players have CEU preferences. The associated ambiguous beliefs are revised by Generalized Bayesian Updating. We assume individuals take account of possible changes in their preferences by using consistent planning. We show that if there is ambiguity in the centipede game it is possible to sustain 'cooperation' for many periods as part of a consistent-planning equilibrium under ambiguity. In a non-cooperative bargaining game we show that ambiguity may be a cause of delay in bargaining.
urn:nbn:de:bsz:16-heidok-233892
Keywords: D81; 330; optimism; neo-additive capacity; dynamic consistency; consistent planning; centipede game; multi-stage game